Neuromuscular disturbances in adolescent idiopathic scoliosis observed from the anticipatory muscle activations in scapula stabilizers: a cross-sectional study - Yu Wang; Nan Xia; Minghui Gu; Zejian Chen; Jiang Xu; Li Wang; Yi Liao; Lingfeng Xie; Xiaolin Huang (BMC Musculoskeletal Disorders)
Abstract Background While it is well-stablished that scoliosis can lead to neuromuscular control disorders, the specific characteristics of these impairments remain unclear. This study aimed to explore the neuromuscular features of scapula stabilizers in adolescents with idiopathic scoliosis (AIS) through an analysis of anticipatory muscle activations (AMAs). Methods A cross-sectional observational study was conducted with 17 AIS and 19 age-matched healthy subjects. Both the AIS and healthy groups performed right and left upper limb reaching tasks at three different heights while surface electromyography monitored the activity of scapular stabilizers. The muscles examined included the bilateral infraspinatus, upper trapezius, lower trapezius, serratus anterior, latissimus dorsi and the anterior deltoid. The incidence, onset latencies, and amplitude of AMAs were compared between the AIS and healthy groups. Results Among scapular stabilizers, ipsilateral upper trapezius (iUT) and ipsilateral infraspinatus (iIS) exhibited the highest AMAs incidence at 72.59% and 70.06%, respectively. However, AMAs incidence significantly declined on the concave side of the thoracic curve in AIS group, particularly in iUT (55.63 ± 14.74 vs. 45.21 ± 19.92, t = 2.330, P = 0.034) and iIS (59.38 ± 20.16 vs. 48.13 ± 22.11, t = 2.316, P = 0.035). Regarding onset latencies, the AIS group exhibited delayed activation of ipsilateral lower trapezius (F = 3.586, P < 0.05, η2 p = 0.006) and advanced activation of contralateral upper trapezius (F = 7.753, P < 0.001, η2 p = 0.027) and contralateral infraspinatus (F = 6.554, P < 0.01, η2 p = 0.024) on concave side compared to the healthy group. Additionally, almost all scapula stabilizers in AIS group exhibited reduction of AMAs amplitude compared to the healthy group. Conclusions This preliminary study suggests potential neuromotor control impairments in the AIS population, as indicated by observed trends in the incidence, amplitude, and timing of AMAs in scapular stabilizers. These preliminary insights may inform the design of future rehabilitation interventions, with attention to neurodevelopmental needs during adolescence. Trial registration number ChiCTR2300075167, Date: 2023-08-28.